Joint Numerical Range of Matrix Polynomials - Ahmed Sabir (Al-Rafidain Journal of Computer Sciences and Mathematics)
Some algebraic properties of the sharp points of the joint numerical range of a matrix polynomials are the main subject of this paper. We also consider isolated points of the joint numerical range of matrix polynomials.